Compatible mappings and common fixed points - Gerald Jungck (International Journal of Mathematics and Mathematical Sciences)
A generalization of the commuting mapping concept is introduced. Properties of this weakened commutativity are derived and used to obtain results which generalize a theorem by Park and Bae, a theorem by Hadzic, and others.